US Rebalancing Strategy in Asia Pacific Region - Mr. Khusrow Akkas Abbasi (CISS Insight Journal, 2014)
President Obama in his foreign policy statements in an address to the Australian parliament in November 2011 and as recently as in May 23, 2014 address at the US Military Academy at West Point, New York has emphasized US rebalancing in the Asia Pacific region. Obama’s emphasis on the Asia Pacific or rebalancing strategy is built on the same grounds, but perhaps on more extensive level, as the policy formulated by George W. Bush. Rebalancing includes efforts to solidify relations with existing regional partners and allies, and negotiating new regional economic arrangements using existing multilateral initiatives like Asia Pacific Economic Cooperation (APEC), the Association of Southeast Asian Nations (ASEAN) ASEAN Regional Forum (ARF) the Trans-Pacific Partnership (TPP), as well as developing new partnerships with emerging powers such as India, Indonesia and Vietnam. Lastly it entails augmenting military capabilities in the southern and western Asia Pacific region primarily through new rotational deployments.Key officials of the Obama administration believe that the US was “underweighted in Asia, given the importance of the region, given the economic dynamism in the region, and the strategic dynamics in the region”. There is no doubt that the rebalancing policy was guided by rising concerns and apprehension over China’s growing influence in the Asia Pacific region.